Stylistic Analysis of Cohesion in Ted Hughes ‘The Wind’ - Ali, Hazim; Abbas, Aswan; Mugair, Sarab (Utopía y Praxis Latinoamericana, 2020)
The study attempts to examine and analyze Ted Hughes’ style in his poem the Wind. The poem is about the natural element, wind, which is described in an unconventional manner. The discussion and results of the study present how Ted Hughes’ language is used in a way to reflect the savagery of the natural element, wind, by the patterns of cohesion and deviation in the poem. Thus, the analysis of the study will enhance the reader’s understanding of the different stylistic features in the poem; they are structure, themes, symbolism and intertextuality.